HMGB2 is a negative regulator of telomerase activity in human embryonic stem and progenitor cells - Kučírek, Martin; Bagherpoor, Alireza J; Jaroš, Josef; Hampl, Aleš; Štros, Michal (The FASEB journal, 2019)
High-mobility group box (HMGB)1 and HMGB2 proteins are the subject of intensive research because of their involvement in DNA replication, repair, transcription, differentiation, proliferation, cell signaling, inflammation, and tumor migration. Using inducible, stably transfected human embryonic stem cells (hESCs) capable of the short hairpin RNA-mediated knockdown (KD) of HMGB1 and HMGB2, we provide evidence that deregulation of HMGB1 or HMGB2 expression in hESCs and their differentiated derivatives (neuroectodermal cells) results in distinct modulation of telomere homeostasis. Whereas HMGB1 enhances telomerase activity, HMGB2 acts as a negative regulator of telomerase activity in the cell. Stimulation of telomerase activity in the HMGB2-deficient cells may be related to activation of the PI3K/protein kinase B/ glycogen synthase kinase-3β/β-catenin signaling pathways by HMGB1, augmented TERT/telomerase RNA subunit transcription, and possibly also because of changes in telomeric repeat-containing RNA (TERRA) and TERRA-polyA+ transcription. The impact of HMGB1/2 KD on telomerase transcriptional regulation observed in neuroectodermal cells is partially masked in hESCs by their pluripotent state. Our findings on differential roles of HMGB1 and HMGB2 proteins in regulation of telomerase activity may suggest another possible outcome of HMGB1 targeting in cells, which is currently a promising approach aiming at increasing the anticancer activity of cytotoxic agents.-Kučírek, M., Bagherpoor, A. J., Jaroš, J., Hampl, A., Štros, M. HMGB2 is a negative regulator of telomerase activity in human embryonic stem and progenitor cells.
Keywords: protein HMGB2; Transfection; kmenové buňky; Telomerase; lidé; telomerasa; Stem Cells; lidské embryonální kmenové buňky; Transcription, Genetic; HMGB2 Protein; Humans; Cell Differentiation; buněčná diferenciace; Human Embryonic Stem Cells; protein HMGB1; genetická transkripce; HMGB1 Protein; transfekce